The signal quality of tripolar Laplacian electrogram compared to bipolar electrogram in cardiac electrophysiology - Soichiro Yamashita; Makoto Takemoto; Wataru Fujimoto; Koji Kuroda; Junichi Imanishi; Masamichi Iwasaki; Takafumi Todoroki; Masanori Okuda (Journal of Arrhythmia, 2025)
Abstract Background The usefulness of tripolar Laplacian electrogram (TLE) in cardiac electrophysiology is unknown. Objective We investigated the difference in the morphology, voltage amplitude, noise level, and far‐field potential (FFP) between TLE and bipolar electrogram (BE). Methods Twenty‐two patients who underwent catheter ablation for atrial fibrillation were analyzed. TLE and BE were simultaneously obtained using 64‐electrode basket catheters during atrial tachycardia or pacing. Local electrograms (EGMs) were analyzed at the locations of three activation patterns: normal conduction, wavefront collision, and slow conduction (SC). In addition, each activation pattern was analyzed at two different wavefront angles: horizontal and vertical, respectively. The voltage amplitude, duration, morphology, and deflection number were compared. The noise level and FFP amplitude were also analyzed. Results With all activation patterns and wavefront angles, the voltage amplitude was significantly lower on TLE than on BE, and the mean amplitude ratio of TLE/BE was 0.75. The duration and deflection number of EGM were comparable. The ventricular FFP amplitude was lower on TLE than on BE (0.04 mV vs. 0.40 mV, p = .01). TLE also had less noise than BE (0.08 mV vs. 0.15 mV, p = .02), with a noise reduction of 47%. At the SC area, low‐voltage EGMs below the mean noise levels were more common with BE than with TLE (29% vs. 8%, p = .04). Conclusion TLE has a lower voltage amplitude than BE for all activation patterns and wavefront angles, and it removes more noise and FFPs. TLE is useful for analyzing low‐voltage and fractionated EGMs regardless of the wavefront angle.